Mechanical Characterization of Human Brain Tissue and Soft Dynamic Gels Exhibiting Electromechanical Neuro‐Mimicry. Issue 10 (3rd April 2019) - Tabet, Anthony; Mommer, Stefan; Vigil, Julian A.; Hallou, Clement; Bulstrode, Harry; Scherman, Oren A.
Abstract: Synthetic hydrogels are an important class of materials in tissue engineering, drug delivery, and other biomedical fields. Their mechanical and electrical properties can be tuned to match those of biological tissues. In this work, hydrogels that exhibit both mechanical and electrical biomimicry are reported. The presented dual networks consist of supramolecular networks formed from 2:1 homoternary complexes of imidazolium‐based guest molecules in cucubit[8]uril and covalent networks of oligoethylene glycol‐(di)methacrylate. The viscoelastic properties of human brain tissues are also investigated. The mechanical properties of the dual network gels are benchmarked against the human tissue, and it is found that they both are neuro‐mimetic and exhibit cytocompatibility in a neural stem cell model. Abstract : Mechanical properties of healthy human brain tissues and human glioma tissues are reported. Soft electronic gels comprised of dual supramolecular and covalent networks mimic these brain tissues' electromechanical properties.